Mistura de óleo mineral e vegetal para uso em transformadores de potência - Coelho Junior, Luiz de Gonzaga (2007)
This paper presents a proposal for dielectric insulating oil formed by the mixture of mineral insulating oil and vegetable oil common for use in electrical power transformers. The primary purpose of the work is to provide a new alternative mixture of insulating oil for transformers composed of mineral oil and soybean oil which keeps the same dielectrics and physical-chemical characteristics of mineral oils in the market. In order to that, were used criteria such as: provision of market, product with a good percentage of non-saturated oleic acids in the composition and product with a low purchase cost. Moreover, were implemented 3 mixtures with different proportions of mineral oils varying from 10% to 50%. The mixture that produced the best index was composed of 90% of mineral insulating oil and 10% of soybean oil common. The results of the tests are presented and then compared to different types of insulating oils available on the market. In the comparisons, has been a focus in vegetable oils currently on the market. In the results presented, the mixture got satisfactory index in standards required by ABNT 5357 and ASTM D3487 for mineral oils. In some assay, such as Pour Point, which obtained -44°C and Acid Number, which got 0.01, values better than those produced by conventional mineral oils have been detached. However, the main advantages presented by this mixture are in the final product cost, which varied with a final reduction of up to 5%. Besides the case study, the dissertation approaches the behavior of the current market of insulating oils emphasizing recent vegetable oils developed at global level. This work also shows future opportunities for deepening and development of new concepts and theories on the subject.